Excellent photocatalytic performance of hydrogenated dark purple Ag/TiO2 catalyst. Issue 10 (24th June 2021) - Du, Mingming; Xu, Geting; Zeng, Ganning; Sheng, Yinxiao; Wang, Jiaqi; Wang, Yuhe; Li, Xiaonian
Abstract: BACKGROUND: Photocatalytic oxidation technology with semiconductor materials has shown great application prospects in environmental protection, energy and other fields. Developing a semiconductor material with high light conversion efficiency is a current scientific frontier problem. RESULTS: A novel dark purple Ag/TiO2 catalyst with small energy gap of 2.27 eV was prepared and characterized using X‐ray diffraction, X‐ray photoelectron spectroscopy, transmission electron microscopy and diffuse reflectance UV–visible (DRUV‐Vis) techniques. Experimental results show that TiO2 phase transformation from anatase to rutile was inhibited in the presence of silver nanoparticles (Ag NPs) during hydrogenation. A surface disordered layer of 0.8–2.0 nm was formed which greatly enhanced light absorption according to DRUV‐Vis spectral analysis. Due to the favorable synergistic effect between Ag NPs and the surface disordered layer of TiO2, the dark purple Ag/TiO2 catalyst showed enhanced photocatalytic degradation activity. After utilization for five cycles, there was no significant decrease in the activity, suggesting high catalytic stability of the novel dark purple Ag/TiO2 catalyst. CONCLUSIONS: The results verify that the novel dark purple Ag/TiO2 catalyst with small energy gap of 2.27 eV has enhanced photocatalytic performance. © 2021 Society of Chemical Industry (SCI).